Breast diseases associated with systemic medical disorders. Issue 4 (April 2017) - Nomikos, Angheliki; Thomas, Jeremy
Abstract: A wide range of systemic disorders may present as breast lesions, in some cases mimicking primary breast carcinoma and other primary breast diseases clinically and radiologically. The distinction between the manifestation of a systemic medical disorder in the breast and primary breast pathology is clinically important as management and follow-up may defer widely. However, apart from diabetes mellitus-associated breast disease, the manifestation of systemic disorders on breast tissue is rare and the general histopathologist is unlikely to encounter this regularly. This review examines the most common benign breast lesions associated with systemic medical disorders and drugs, including the typical clinical and radiological findings, pathogenesis, and macroscopic and microscopic findings. The specific features and immunohistochemical techniques helpful in differentiating benign disease from carcinoma will be discussed and illustrated using examples from our own practice.